PECULIARITIES OF THE ORGANIZATION AND DIRECTIONS OF IMPROVEMENT OF ACCOUNTS RECEIVABLES - Berzhanir , I. А. (The actual problems of regional economy development, 2022)
The purpose of the article is to study theoretical provisions and development of practical recommendations for improving the accounting process of calculations of business entities in modern conditions. In the course of the study, the following methods are used: historical – in the study of genesis, the notion of «accounts receivable»; methods of induction and deduction, method of comparison, method of generalization – for the disclosure and clarification of the economic entity of receivables and its classification for accounting; grouping method – to improve the classification of receivables; system approach – for the construction of accounting control of receivables; statistical methods of research – for assessing the structure and dynamics of the receivables of the enterprise; graphic – for a visual representation of research results. The information base of scientific research is the scientific works of domestic scientists-economists and regulatory acts on accounting. The article deals with the economic essence of the receivables of the enterprise, as well as the preconditions for its emergence in modern economic conditions. The classification features on receivables are reflected. The diagnosis of composition and structure of the receivables of the enterprise was conducted and the factors influenced by its change. The theoretical and methodological foundations of the accounting of receivables are considered. It has been established that for efficient management of payments with buyers and customers there is a need for objective information, first of all in the detail of accounting data with buyers and customers in order to control them. The scientific novelty of the results obtained is to determine and disclose the directions of improvement of the accounting of receivables through the creation of a reserve of doubtful debts, conducting systematic inventory of debt, accelerating the repayment of receivables with the help of modern forms of its refinancing, etc. The results of the research obtained can be used to create an effective model of accounting, which will enable the risk of insolvency and reducing liquidity risks as a result of obtaining objective and timely information for the adoption of managerial decisions.